Three-layer structural color multilayer structure

By adopting three-layer structure and ALD technology in multi-layer structure pigments, the problem of high production cost of existing multi-layer structure pigments is solved, efficient and low-cost pigment production is achieved, and the quality of the layer is improved.

CN119816762AInactive Publication Date: 2025-04-11TOYOTA JIDOSHA KK
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202380062760.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-03-02
Filing Date
2023-09-07
Publication Date
2025-04-11
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Existing multilayer structural pigments require multiple film layers to achieve the desired color characteristics, resulting in high production costs.

Method used

A multi-layer structure with a three-layer structure, including a core layer, a conformal dielectric layer and a conformal absorbing layer, is deposited through atomic layer deposition (ALD) technology to reduce the number of layers and improve the quality of the layer.

Benefits of technology

The same optical properties as the multi-layer structure are achieved, but only three layers are required, reducing manufacturing cost and time while improving the density and coverage of the layers.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119816762A_ABST
    Figure CN119816762A_ABST
Patent Text Reader

Abstract

A color reflecting multilayer structure includes a core layer and a conformal dielectric layer encapsulating the core layer. The conformal absorber layer encapsulates the conformal dielectric layer. The multilayer structure is composed of three optical layers.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] CROSS-REFERENCE TO RELATED APPLICATIONS

[0002] This application claims the benefit of priority under 35 USC §119 to U.S. Provisional Application Serial No. 63 / 404,416, filed on September 7, 2022, the contents of which are relied upon herein and are incorporated herein by reference in their entirety. Technical Field

[0003] The present disclosure relates to multilayer structures, and in particular to multilayer structures comprising a metal and a metal oxide on a substrate, wherein at least one of the metal and the metal oxide is deposited by atomic layer deposition. Background Art

[0004] Pigments made of multilayer structures are known. In addition, pigments that show or provide structural colors are also known. However, such prior art pigments require nine, eleven or more film layers to obtain the desired color properties.

[0005] It will be appreciated that the costs involved in the production of multilayer pigments are proportional to the number of layers required. Therefore, the costs involved in producing structural colors using multilayer stacks of dielectric materials may be prohibitive. Therefore, structural colors that require the least number of thin film layers would be desirable. Summary of the invention

[0006] According to an embodiment, a color-reflecting multilayer structure includes: a core layer; a conformal dielectric layer encapsulating the core layer; and a conformal absorbing layer encapsulating the conformal dielectric layer, wherein the multilayer structure consists of three optical layers.

[0007] According to an embodiment, a method for forming a multilayer structure includes depositing a conformal dielectric layer on a core layer by CVD or ALD; and depositing a conformal absorber layer on the conformal dielectric layer by ALD.

[0008] Additional features and advantages will be set forth in the following detailed description, and in part will be apparent to those skilled in the art from that description or may be learned by practicing the embodiments described herein, including the following detailed description, claims, and accompanying drawings.

[0009] It should be understood that both the foregoing general description and the following detailed description describe multiple embodiments and are intended to provide an overview or framework for understanding the nature and character of the claimed subject matter. The accompanying drawings are included to provide a further understanding of the various embodiments and are incorporated into and constitute a part of this specification. The accompanying drawings illustrate multiple embodiments described herein and, together with the description, serve to explain the principles and operation of the claimed subject matter. BRIEF DESCRIPTION OF THE DRAWINGS

[0010] Figure 1 is a schematic cross-sectional view of a multilayer structure according to embodiments disclosed and described herein;

[0011] Figure 2A depicts a multilayer structure having a dielectric layer extending over a core layer for use in the design of the multilayer structure;

[0012] Figure 2B depicts a multilayer structure having an absorbent layer extending over a core layer for use in the design of the multilayer structure;

[0013] Figure 2C depicts a multilayer structure having a dielectric layer extending over a core layer for use in the design of a multilayer structure according to one or more embodiments shown and described herein;

[0014] Figure 3 Depicted FIG. 2A to FIG. 2C Reflectance characteristics of the multilayer structure shown in Lab color space;

[0015] Figure 4A Graphically depicts Figure 2A Chromaticity and hue values ​​of the multilayer structure shown as a function of dielectric layer thickness;

[0016] Figure 4B Graphically depicts Figure 2B Chromaticity and hue values ​​of the multilayer structures shown as a function of the thickness of the semiconductor absorber layer;

[0017] Figure 4C Graphically depicts Figure 2C Chromaticity and hue values ​​of the multilayer structure shown as a function of dielectric layer thickness;

[0018] Figure 5 depicts a multilayer structure having a dielectric layer extending over a substrate layer and exposed to electromagnetic radiation at an angle θ relative to a normal direction to an outer surface of the dielectric layer;

[0019] Fig. 6A is a graph of reflectivity versus wavelength of electromagnetic radiation showing the effect of the thickness of the tungsten absorbing layer; and

[0020] Figure 6B is a graph of reflectivity versus wavelength of electromagnetic radiation showing the effect of the thickness of the TiO2 dielectric layer. DETAILED DESCRIPTION

[0021] Color-producing structures are provided in the present disclosure. The color-producing structures have the form of multilayer structures that can reflect narrow-band electromagnetic radiation in the visible spectrum and have a small or insignificant hue shift when the multilayer structures are viewed from an angle of 0 to 45 degrees. The multilayer structures can be used as pigments in compositions (e.g., coating compositions), films on structures, and the like.

[0022] The preparation of color multilayer structures can be a complex, expensive process, in part because very tight control over layer thickness is required. The deposition methods used to deposit the layers can vary in complexity and cost, depending on the materials that make up a given layer and the desired layer thickness. As a result, the materials that make up a given layer and the desired layer thickness vary.

[0023] However, it can be challenging to deposit layers directly onto a reflective core layer, such as an aluminum (Al) reflective core, and it can be difficult to deposit materials in layers with nanometer-scale thicknesses. Atomic layer deposition (ALD) is a technique that excels in both of these aspects, but ALD deposition has been costly and time-consuming to date. For example, ALD essentially deposits materials at the atomic level, so depositing thick layers, such as layers greater than 500 nm thick, using an ALD process can take a lot of time. Therefore, ALD is generally not preferred for depositing each layer in a multilayer structure. Typically, due to cost and time constraints, ALD is dedicated to depositing very thin layers, and layers applied by previous ALD methods produce low-quality layers that may have poor coverage or high porosity, which makes it difficult to apply additional high-quality metal and / or metal oxide layers to the multilayer structure.

[0024] However, as disclosed herein, it has been discovered that depositing all of the layers of a multilayer structure using ALD provides layers with properties (e.g., surface area and pore volume) that can allow a microlayer structure having three layers to perform in the same manner as a multilayer structure having significantly more layers. Specifically, embodiments disclosed herein use an ALD process to deposit dense, non-porous metal and / or metal oxide layers to a reflector (e.g., Al). The quality of the layers deposited by ALD allows for a three-layer OSC multilayer structure having optical properties similar to five-layer and seven-layer OSC multilayer structures. By reducing the number of layers deposited to the multilayer structure, manufacturing costs and time can be reduced.

[0025] The multilayer structures described herein can be used to reflect visible light wavelengths over a range of incident angles or viewing angles (e.g., hues between 0° and 120°). It will be understood that the terms "electromagnetic wave," "electromagnetic radiation," and "light" as used herein can interchangeably refer to light of various wavelengths incident on the multilayer structure, and that such light can have wavelengths in the ultraviolet (UV), infrared (IR), and visible portions of the electromagnetic spectrum.

[0026] As used herein, "core layer" refers to a reflective core layer and a non-reflective core layer, and the "core layer" may have any shape, including but not limited to a sheet, a sphere, an oval, etc. As used herein, "absorption layer" includes a metal absorption layer and a non-metal absorption layer.

[0027] Now refer to Figure 1 , the multilayer structure 100 according to the embodiments disclosed and described herein includes a core layer 110, a conformal dielectric layer 120 encapsulating the core layer 110, and a conformal absorbing layer 130 encapsulating the conformal dielectric layer 120. The multilayer structure 100 disclosed and described herein consists of three optical layers. These "optical layers" are layers that affect the optical properties of the multilayer structure 100, such as layers made of reflective materials, dielectric materials, and absorbing materials, wherein the layers are thick enough to affect the optical properties of the multilayer structure. The term "optical layer" as used herein does not include thin barrier layers that do not affect the optical properties of the multilayer structure.

[0028] Reference FIG. 2A to FIG. 2C and Figure 3 , depicts the effectiveness of different types of layers extending over the core layer 110 in achieving desired hue levels in desired regions of the visible light spectrum as plotted or displayed on Lab color space. Figure 2A A ZnS dielectric layer 120a extending over the reflective core layer 110 is depicted, Figure 2B depicts a Si semiconductor absorber layer 120b extending over the reflective core layer 110, and Figure 2C A Fe2O3 dielectric layer 120c is depicted extending over the reflective core layer 110. FIG. 2A to FIG. 2C The reflectivity of each multilayer structure shown is simulated as a function of different thicknesses of dielectric layer 120a, semiconductor absorber layer 120b, and dielectric layer 120c. The results of the simulation are plotted on the Lab color space, also known as the a*b* color diagram, as shown in Figure 3 middle. Figure 3 The individual data points shown provide Figure 2A The dielectric layer of the multilayer structure depicted in Figure 2B The semiconductor absorber layer of the multilayer structure depicted in FIG. Figure 2C Chroma and hue of the dielectric layers of the multilayer structure depicted in Figure 1. Chroma can be defined as And the hue can be defined as tan -1 (a* / b*). Hue can also be referred to as the angle of a given data point relative to the positive a* axis. Hue values ​​provide a measure of the color (e.g., red, green, blue, yellow, etc.) an object appears to have, and chromaticity values ​​provide a measure of the "brightness" of a color. Figure 3 As shown, Figure 2B and Figure 2C Compared with the multilayer structure shown, Figure 2A The multilayer structure shown provides low chroma. FIG. 2A to FIG. 2C and Figure 3 It is shown that when a color with high chroma is desired, an absorbing layer is preferred over a dielectric layer as the first layer extending over a reflective core layer. It is understood that Figure 3 The Lab color space analysis shown in is for illustrative purposes, and the multilayer structure according to the embodiments disclosed and described herein can have different Lab color space values. For example, in an embodiment, the multilayer structure can show blue, green, yellow or other colors in the Lab color space.

[0029] Reference FIG. 4A to FIG. 4C , which plots chroma and hue as a function of layer thickness. Specifically, Figure 4A Graphically depicts chroma and hue as Figure 2A Shown is a function of the thickness of the ZnS dielectric layer extending over the Al reflective core layer. Figure 4B Describes chroma and hue as Figure 2B Shown is a function of the thickness of the Si semiconductor absorber layer extending on the Al reflective core layer. Figure 4C Describes chroma and hue as Figure 2C Shown is a function of the thickness of the Fe2O3 dielectric layer extending over the Al reflective core layer. FIG. 4A to FIG. 4C The dashed line in corresponds to the desired hue value from 10° to 30° on the Lab color space. FIG. 4A to FIG. 4C It is shown that the multilayer structure having a dielectric layer extending over a reflective core layer achieves higher chromaticity values ​​in the hue range of 10° to 30°. Likewise, it should be understood that FIG. 4A to FIG. 4C The hues and chromas shown in are for illustrative purposes, and multi-layer structures according to embodiments disclosed and described herein may have different hue and chroma values.

[0030] Refer again Figure 1 , shows a multilayer structure 100 of reflective color according to an embodiment. The multilayer structure 100 includes a core layer 110, a conformal dielectric layer 120 encapsulating the core layer 110, and a conformal absorption layer 130 encapsulating the conformal dielectric layer 120. Figure 1 As shown, embodiments of the multilayer structures disclosed and described herein include a conformal dielectric layer 120 and a conformal absorber layer 130. As used herein, "conformal" is used to indicate that a layer conforms to the size and shape of the layer onto which it is deposited and encapsulates (i.e., is present on all sides) the layer onto which it is deposited. Figure 1 A rectangular structure is shown, but this is for illustration purposes only, and the multilayer structure generally has an asymmetric and non-uniform shape. In embodiments, the multilayer structure may be spherical or oval. It should be understood that embodiments may also include a multilayer structure having a conformal absorber encapsulating a core layer and a conformal dielectric layer encapsulating a conformal absorber layer.

[0031] In an embodiment, the thickness of the core layer 110 may be greater than or equal to 20 nm and less than or equal to 100 μm, for example, greater than or equal to 50 nm and less than or equal to 80 μm, greater than or equal to 75 nm and less than or equal to 60 μm, greater than or equal to 100 nm and less than or equal to 40 μm, greater than or equal to 125 nm and less than or equal to 20 μm, or greater than or equal to 150 nm and less than or equal to 1 μm. In an embodiment, the thickness of the core layer 110 may be 50 nm to 10 μm, for example, 100 nm to 10 μm, 250 nm to 10 μm, 500 nm to 10 μm, 750 nm to 10 μm, 1 μm to 10 μm, 2 μm to 10 μm, 5 μm to 10 μm, 8 μm to 10 μm, 50 nm to 8 μm, 100 nm to 8 μm, 250 nm to 8 μm, 500 nm to 8 μm, 750 nm to 8 μm, 1 μm to 8 μm, 2 μm to 8 μm, 5 μm to 8 μm, 50 nm to 5 μm, 100 nm to 5 μm, 250 nm to 5 μm, 500 nm to 5 μm, 750 nm to 5 μm, 1 μm to 10 μm, 2 μm to 10 μm, 5 μm to 10 μm, 8 μm to 10 μm, 5μm, 2μm to 5μm, 50nm to 2μm, 100nm to 2μm, 250nm to 2μm, 500nm to 2μm, 750nm to 2μm, 1μm to 2μm, 50nm to 1μm, 100nm to 1μm, 250nm to 1μm, 500nm to 1μm, 750nm to 1μm, 50nm to 750nm, 100nm to 750nm, 250nm to 750nm, 500nm to 750nm, 50nm to 500nm, 100nm to 500nm, 250nm to 500nm, 50nm to 250nm, 100nm to 250nm, or 50nm to 100nm.

[0032] In an embodiment, the core layer 110 may be made of at least one of a "gray metal" material (e.g., Al, Ag, Pt, Sn); at least one of a "color metal" material (e.g., Au, Cu, brass, bronze, TiN, Cr, stainless steel), or a combination thereof. In one or more embodiments, the core layer 110 may be made of an oxide, such as aluminum oxide (Al2O3), silicon dioxide (SiO2), or a glass material. As described above, the core layer 110 may have a plate-like shape or may be spherical or oval.

[0033] According to one or more embodiments, the thickness of the conformal dielectric layer 120 is greater than or equal to 5 nm and less than or equal to 500 nm, for example, greater than or equal to 10 nm and less than or equal to 475 nm, greater than or equal to 10 nm and less than or equal to 450 nm, greater than or equal to 10 nm and less than or equal to 425 nm, greater than or equal to 10 nm and less than or equal to 400 nm, greater than or equal to 10 nm and less than or equal to 375 nm, greater than or equal to 10 nm and less than or equal to 350 nm, greater than or equal to 10 nm and less than or equal to 325 nm, or greater than or equal to 10 nm and less than or equal to 300 nm. According to an embodiment, the thickness of the conformal dielectric layer 120 may be 5 nm to 300 nm, for example, 10 nm to 300 nm, 15 nm to 300 nm, 25 nm to 300 nm, 50 nm to 300 nm, 75 nm to 300 nm, 100 nm to 300 nm, 125 nm to 300 nm, 150 nm to 300 nm, 175 nm to 300 nm, 200 nm to 300 nm, 225 nm to 300 nm, 250 nm to 300 nm, 275 nm to 300 nm, 50 nm to 300 nm, 100 nm to 300 nm, 125 nm to 300 nm, 150 nm to 300 nm, 175 nm to 300 nm, 200 nm to 300 nm, 225 nm to 300 nm, 250 nm to 300 nm, 27 ... 275nm, 100nm to 275nm, 125nm to 275nm, 150nm to 275nm, 175nm to 275nm, 200nm to 275nm, 225nm to 275nm, 250nm to 275nm, 5nm to 250nm, 10nm to 250nm, 15nm to 250nm, 25nm to 250nm, 50nm to 250nm, 75nm to 275nm 250nm, 100nm to 250nm, 125nm to 250nm, 150nm to 250nm, 175nm to 250nm, 200nm to 250nm, 225nm to 250nm, 5nm to 225nm, 10nm to 225nm, 15nm to 225nm, 25nm to 225nm, 50nm to 225nm, 75nm to 225nm, 100nm to 225nm, 125nm to 225nm, 150nm to 225nm, 175nm to 225nm, 200nm to 225nm, 5nm to 200nm, 10nm to 200nm, 15nm to 200nm, 25nm to 200nm, 50nm to 200nm, 75nm to 200nm, 100nm to 200nm, 125nm to 200nm, 150nm to 200nm, 175nm to 200nm, 5nm to 175nm, 10nm to 175nm, 15nm to 175nm, 25nm to 175nm, 50nm to 175nm, 75nm to 175nm, 100nm to 175nm,125nm to 175nm, 150nm to 175nm, 5nm to 150nm, 10nm to 150nm, 15nm to 150nm, 25nm to 150nm, 50nm to 150nm, 75nm to 150nm, 100nm to 150nm, 125nm to 150nm, 5nm to 100nm, 10nm to 100nm, 15nm to 100nm, 25nm to 100nm, 50nm to 1 100nm, 75nm to 100nm, 5nm to 75nm, 10nm to 75nm, 15nm to 75nm, 25nm to 75nm, 50nm to 75nm, 5nm to 50nm, 10nm to 50nm, 15nm to 50nm, 25nm to 50nm, 5nm to 25nm, 10nm to 25nm, 15nm to 25nm, 5nm to 15nm, 10nm to 15nm, or 5nm to 10nm.

[0034] In an embodiment, the conformal dielectric layer 120 is a high refractive index material, such as TiO2 (including anatase, rutile or amorphous TiO2 and mixtures thereof), ZnS, ZrO2, HfO2, Fe3O4 or AlAs. In one or more embodiments, the conformal dielectric layer 120 may be made of a high refractive index absorptive dielectric material, such as Fe2O3, PbS, GaAs or InAs. In an embodiment, the conformal dielectric layer may be made of a low refractive index material, such as SiO2, MgF2, KBr, ZnO or Al2O3. In an embodiment, the conformal dielectric layer 120 may be deposited by CVD, PVD, wet chemical method or ALD to encapsulate the core layer 110.

[0035] like Figure 1 As shown, conformal absorber layer 130 encapsulates conformal dielectric layer 120. The location of conformal absorber layer 130 is selected to increase absorption of the target wavelength of light. For example, if the multilayer structure is to be configured to absorb electromagnetic radiation having a wavelength less than or equal to 550 nm, but reflect electromagnetic radiation having a wavelength of approximately 650 nm, such as visible light outside the 10° to 30° hue, the absorber layer is positioned such that the electric field (|E| 2 ) at a wavelength of 550nm is less than at a wavelength of 650nm. Mathematically, this can be expressed as:

[0036] |E 550 | 2 <<|E 650 | 2 (1)

[0037] And preferably:

[0038] |E 650 | 2 ≈0 (2)

[0039] According to the implementation scheme, Figure 5 and the following discussion provides a method for calculating the thickness of a zero electric field point or near zero electric field point at a given wavelength of light. For the purposes of this specification, the term "near zero" is defined as |E| 2 ≤10. Figure 5 shows that the refractive index is "n s " is a multilayer structure of a dielectric layer 4 on a substrate layer 2, wherein the dielectric layer 4 has a total thickness "D", an incremental thickness "d" and a refractive index "n". The substrate layer 2 can be a core layer or a reflective core layer of the multilayer structure. The incident light strikes the outer surface 5 of the dielectric layer 4 at an angle θ relative to a line 6 perpendicular to the outer surface 5, and is reflected from the outer surface 5 at the same angle θ. The incident light strikes the outer surface 5 of the dielectric layer 4 at an angle θ relative to the line 6 F Passing through the outer surface 5 and entering the dielectric layer 4, and at an angle θ S The surface 3 of the base layer 2 is illuminated. For a single dielectric layer, θ S =θ F , and when z = d, the energy / electric field (E) can be expressed as E(z). According to Maxwell's equations, for s-polarization, the electric field can be expressed as:

[0040]

[0041] And for p polarization, it is expressed as:

[0042]

[0043] in λ is the desired reflection wavelength, α = n s sinθ s , where "s" corresponds to the basis in Figure 7, and is the dielectric constant of the layer as a function of z. Therefore:

[0044] For s-polarization,

[0045] |E(d)| 2 =|u(z)| 2 exp(2ikay)| z=d (5)

[0046] as well as

[0047] For p polarization,

[0048]

[0049] It should be understood that the change of the electric field along the Z direction of the dielectric layer 4 can be estimated by calculating the unknown parameters u(z) and v(z), which can be shown as:

[0050]

[0051] where "i" is the square root of -1. Using the boundary condition u| z=0 =1,v| z=0 =q s and the following relationship:

[0052] For s-polarization, q s =n s cosθ s (8)

[0053] For p polarization, q s =n s / cosθ s (9)

[0054] For s-polarization, q = n cosθ F (10)

[0055] For p polarization, q = n / cosθ F (11)

[0056]

[0057] u(z) and v(z) can be expressed as:

[0058]

[0059] and

[0060]

[0061] therefore:

[0062] For s-polarization,

[0063]

[0064] in as well as:

[0065] For p polarization,

[0066]

[0067] in:

[0068] α=n s sinθ s = n sinθ F (17)

[0069]

[0070] as well as

[0071]

[0072] Therefore, for θ F = 0 or normal incidence, And the simple case of α = 0: s-polarized |E(d)| 2 = p-polarized

[0073]

[0074] This allows the thickness "d" (i.e., the location or position within the dielectric layer where the electric field is zero) to be solved. It should be understood that the thickness "d" can be such a thickness of the conformal dielectric layer 120 extending on the core layer 110 that provides a zero electric field or a near-zero electric field at the interface between the conformal dielectric layer 120 and the conformal absorber layer 130. It should also be understood that the thickness "d" can also be such a thickness of the dielectric outer layer 140 extending on the conformal absorber layer 130 that provides a zero electric field or a near-zero electric field at the interface between the dielectric outer layer and the conformal absorber layer 130, depending on the thickness "d" at which the electric field is zero or near zero.

[0075] In an embodiment, the thickness of the conformal absorption layer is greater than or equal to 2 nm and less than or equal to 50 nm, for example, greater than or equal to 2 nm and less than or equal to 45 nm, greater than or equal to 2 nm and less than or equal to 40 nm, greater than or equal to 2 nm and less than or equal to 35 nm, greater than or equal to 2 nm and less than or equal to 30 nm, or greater than or equal to 2 nm and less than or equal to 25 nm. In an embodiment, the thickness of the conformal absorber layer 130 can be 2nm to 20nm, for example, 5nm to 20nm, 8nm to 20nm, 10nm to 20nm, 12nm to 20nm, 15nm to 20nm, 18nm to 20nm, 2nm to 18nm, 5nm to 18nm, 8nm to 18nm, 10nm to 18nm, 12nm to 18nm, 15nm to 18nm, 2nm to 15nm, 5nm to 15nm, 8nm to 15nm, 10nm to 15nm, 12nm to 15nm, 2nm to 12nm, 5nm to 12nm, 8nm to 12nm, 10nm to 12nm, 2nm to 10nm, 5nm to 10nm, 8nm to 10nm, 2nm to 8nm, 5nm to 8nm, or 2nm to 5nm.

[0076] In an embodiment, conformal absorber layer 130 may be made of at least one material selected from the group consisting of W, Cr, Ge, Ni, stainless steel, Pd, Ti, Si, V, TiN, Co, Mo, Nb, iron oxide, or a combination thereof. In one or more embodiments, conformal absorber layer 130 comprises W. In an embodiment, ALD is used to deposit conformal absorber layer 130 because ALD allows uniform deposition of materials at a desired thickness. Other deposition methods have difficulty depositing uniform layers with a thickness of 20 nm and below.

[0077] In one or more embodiments, the core layer 110, the first conformal dielectric layer 120, the conformal absorber layer 130, and the second conformal dielectric layer 140 each independently have a thickness less than or equal to 0.030 cm 3 / g, for example, less than or equal to 0.025cm 3 / g, less than or equal to 0.020cm 3 / g, or less than or equal to 0.015cm 3 In an embodiment, the core layer 110, the conformal dielectric layer 120, and the conformal absorber layer 130 each independently have a pore volume of less than or equal to 0.010 cm 3 / g pore volume, for example, less than or equal to 0.009 cm 3 / g, less than or equal to 0.008cm 3 / g, less than or equal to 0.007cm 3 / g, less than or equal to 0.006cm 3 / g, less than or equal to 0.005cm 3 / g, less than or equal to 0.004cm 3 / g, less than or equal to 0.003cm 3 / g, less than or equal to 0.002cm 3 / g, less than or equal to 0.001cm 3 It should be understood that in embodiments, one or more of the core layer 110, the conformal dielectric layer 120, and the conformal absorber layer 130 may have the same pore volume, while in other embodiments, one or more of the core layer 110, the conformal dielectric layer 120, and the conformal absorber layer 130 may have different pore volumes.

[0078] In one or more embodiments, the surface area of ​​each of the core layer 110, the first conformal dielectric layer 120, the conformal absorber layer 130, and the second conformal dielectric layer 140 is independently less than or equal to 100 m2 / g (m 2 / g), for example, less than or equal to 90m 2 / g, less than or equal to 85m 2 / g, less than or equal to 80m 2 / g, less than or equal to 75m 2 / g, less than or equal to 70m 2 / g, less than or equal to 65m 2 / g, less than or equal to 60m 2 / g, less than or equal to 55m 2 / g, less than or equal to 50m 2 / g, less than or equal to 45m 2 / g, less than or equal to 40m 2 / g, less than or equal to 35m 2 / g, less than or equal to 30m 2 / g, less than or equal to 25m 2 / g, less than or equal to 20m 2 / g, or less than or equal to 15m 2 In an embodiment, the surface area of ​​each of the core layer 110, the conformal dielectric layer 120, and the conformal absorber layer 130 is independently less than or equal to 10 m 2 / g, for example, less than or equal to 9m 2 / g, less than or equal to 8m 2 / g, less than or equal to 7m 2 / g, less than or equal to 6m 2 / g, less than or equal to 5m 2 / g, less than or equal to 4m 2 / g, less than or equal to 3m 2 / g, less than or equal to 2m 2 / g, or less than or equal to 1m 2 / g. Therefore, in embodiments, the surface area of ​​each layer may be independently 2m 2 / g to 10m 2 / g, 3m 2 / g to 10m 2 / g, 3m 2 / g to 8m 2 / g, 5m 2 / g to 8m 2 / g, 1m 2 / g to 3m 2 / g, 3m 2 / g to 5m 2 / g, 2m 2 / g to 3m 2 / g, 1m 2 / g to 2m 2 / g, or 0.5m 2 / g to 1m 2 / g. The surface area is measured by collecting a complete adsorption / desorption isotherm of the sample after degassing at 90° C. for 1 hour and at 150° C. for 3 hours. It should be understood that in embodiments, one or more of the core layer 110, the conformal dielectric layer 120, and the conformal absorber layer 130 may have the same surface area, while in other embodiments, one or more of the core layer 110, the conformal dielectric layer 120, and the conformal absorber layer 130 may have different surface areas.

[0079] Isotherms were collected using nitrogen physical adsorption at 76 K, and the specific surface area (SSA) of the material was obtained by fitting 13 points collected from P / P0≈0.06 to 0.3 to the Brunauer-Emmett-Teller (BET) equation. Additional adsorption points were collected at different P / P0 until P / P0≈0.95, followed by desorption back to P / P0≈0.06. The total pore volume was determined by the volume of nitrogen adsorbed at P / P0 0.95, and the average pore size was calculated using the Barrett JoynerHalenda (BJH) method.

[0080] In an embodiment, the multilayer structure may have a D measured by the BET equation. 50 The BET D is the diameter of the adsorbed gas that forms a monolayer on the surface. The amount of molecules in the monolayer multiplied by the space required for one molecule gives 50, is 1 μm to 500 μm, for example, 10 μm to 500 μm, 20 μm to 500 μm, 25 μm to 500 μm, 50 μm to 500 μm, 100 μm to 500 μm, 150 μm to 500 μm, 200 μm to 500 μm, 250 μm to 500 μm, 300 μm to 500 μm, 350 μm to 500 μm, 400 μm to 500 μm, 450 μm to 500 μm, 5 μm to 450 μm, 10 μm to 450 μm, 20 μm to 450 μm, 25μm to 450μm, 50μm to 450μm, 100μm to 450μm, 150μm to 450μm, 200μm to 450μm, 250μm to 450μm, 300μm to 450μm, 350μm to 450μm, 400μm to 450μm, 5μm to 400μm, 10μm to 400μm, 20μm to 400μm, 25μm to 400μm, 50μm to 400μm, 100μm to 400μm, 150μm to 400μm, 200 25μm to 350μm, 50μm to 350μm, 100μm to 350μm, 150μm to 350μm, 200μm to 350μm, 250μm to 350μm, 300μm to 350μm, 5μm to 300μm, 10μm to 300μm, 20μm to 300μm, 25μm to 300μm, 50μm to 300μm, 100μm to 3 00μm, 150μm to 300μm, 200μm to 300μm, 250μm to 300μm, 5μm to 250μm, 10μm to 250μm, 20μm to 250μm, 25μm to 250μm, 50μm to 250μm, 100μm to 250μm, 150μm to 250μm, 200μm to 250μm, 5μm to 200μm, 1 0μm to 200μm, 20μm to 200μm, 25μm to 200μm, 50μm to 200μm, 100μm to 200μm, 150μm to 200μm, 5μm to 150μm, 10μm to 150μm, 20μm to 150μm, 25μm to 150μm, 50μm to 150μm, 100μm to 150μm, 5μm to 100μm , 10μm to 100μm, 20μm to 100μm, 25μm to 100μm, 50μm to 100μm, 5μm to 50μm, 10μm to 50μm, 20μm to 50μm, 25μm to 50μm, 5μm to 25μm, 10μm to 25μm, 20μm to 25μm, 5μm to 20μm, 10μm to 20μm, or 5μm to 10μm.

[0081] The aspect ratio of the multilayer structures according to the embodiments disclosed and described herein is 1 to 100, e.g., 5 to 100, 10 to 100, 20 to 100, 30 to 100, 40 to 100, 50 to 100, 60 to 100, 70 to 100, 80 to 100, 90 to 100, 5 to 90, 10 to 90, 20 to 90, 30 to 90, 40 to 90, 50 to 90, 60 to 90, 70 to 90, 80 to 90, 5 to 80, 10 to 80, 20 to 90, 30 to 90, 40 to 90, 50 to 90, 60 to 90, 70 to 90, 80 to 90, 5 to 80, 10 to 80, 20 to 90, 30 to 90, 40 to 90, 50 to 90, 60 to 90, 70 to 90, 80 to 90, 5 to 80, 10 to 80, 20 to 90, 30 to 50, 40 to 50, 50 to 60, 10 to 40, 20 to 40, 30 to 40, 10 to 40, 20 to 40, 30 to 40, 10 to 40, 20 to 40, 30 to 40, 5 to 30, 10 to 30, 20 to 30, 5 to 20, 10 to 20, or 5 to 10.

[0082] When viewed at an angle of 0° to 45°, embodiments of the multilayer structure 100 described above may have a hue shift in the Lab color space of less than 30°, such as less than 25°, less than 20°, less than 15°, or less than 10°.

[0083] In one or more embodiments, the multilayer structure 100 includes a reflective core layer 110 made of Al, a conformal dielectric layer 120 deposited by ALD and made of TiO2 encapsulating the reflective core layer 110, and a conformal metal absorption layer 130 deposited by ALD and made of W encapsulating the conformal dielectric layer 120.

[0084] In one or more embodiments, the multilayer structure 100 includes a reflective core layer 110 made of Al, a conformal dielectric layer 120 deposited by ALD and made of Fe2O3 encapsulating the reflective core layer 110, and a conformal metal absorption layer 130 deposited by ALD and made of W encapsulating the conformal dielectric layer 120.

[0085] The multilayer structure in the embodiments disclosed herein can be used as a pigment (e.g., a coating pigment for a coating of a brushed object), or a continuous structure applied to an object. When used as a pigment, at least one of a coating binder and a filler can be used and mixed with the pigment to provide a coating showing an omnidirectional structural color. In addition, other additives can be added to the multilayer structure to help the compatibility of the multilayer structure in the coating system. Exemplary compatibility enhancing additives include silane surface treatment agents, which coat the outside of the multilayer structure and improve the compatibility of the multilayer structure in the coating system. Such a coating system or film can be used for any product, including motor vehicles.

[0086] As mentioned herein, at least one of the metal or metal oxide layers (eg, the conformal dielectric layer and the conformal absorber layer) may be deposited by ALD. Embodiments of ALD processes for depositing these layers will be discussed in more detail below.

[0087] Furthermore, the use of the ALD process allows for the large-scale deposition of multiple layers with optical precision and large material property differences (e.g., dielectric materials versus metallic materials as described above). Furthermore, the ALD process allows for the production of multilayer structures with high density, low porosity, and complete layer coverage, all with nanometer-scale precision. Furthermore, the deposition precision and non-destructive nature of ALD has little impact on existing vulnerable layers (e.g., Al core layers, etc.). Such results are difficult or costly to achieve with other processes.

[0088] A first aspect includes a reflective color multilayer structure comprising: a core layer; a conformal dielectric layer encapsulating the core layer; and a conformal absorbing layer encapsulating the conformal dielectric layer, wherein the multilayer structure consists of three optical layers.

[0089] The second aspect comprises a multilayer structure according to the first aspect, wherein the multilayer structure reflects a single narrow band of visible light when exposed to broadband electromagnetic radiation, the single narrow band of visible light comprising: when the multilayer structure is exposed to the broadband electromagnetic radiation and observed from an angle of 0° to 45° relative to the normal direction of the outer surface of the multilayer structure, the single narrow band of visible light has a color shift measured in the Lab color space of less than 30°.

[0090] The third aspect includes the multilayer structure of the first or second aspect, wherein the core layer is formed of Al, Ag, Pt, Sn, Au, Cu, brass, bronze, stainless steel, TiN, Cr, Al2O3, SiO2, glass or a combination thereof.

[0091] A fourth aspect includes the multilayer structure according to the first to third aspects, wherein the thickness of the core layer is 20 nm to 100 μm.

[0092] The fifth aspect includes a multilayer structure according to the first to fourth aspects, wherein the conformal dielectric layer is formed by TiO2, ZnS, ZrO2, HfO2, Fe3O4, AlAs, Fe2O3, PbS, GaAs, InAs, SiO2, MgF2, KBr, ZnO, Al2O3 and combinations thereof.

[0093] A sixth aspect includes the multilayer structure according to the first to fifth aspects, wherein the thickness of the conformal dielectric layer is 5 nm to 500 nm.

[0094] The seventh aspect includes a multilayer structure according to the first to sixth aspects, wherein the conformal absorption layer is formed by W, Cr, Ge, Ni, stainless steel, Pd, Ti, Si, V, TiN, Co, Mo, Nb, iron oxide or a combination thereof.

[0095] An eighth aspect includes the multilayer structure according to the first to seventh aspects, wherein the thickness of the conformal absorber layer is 2 nm to 50 nm.

[0096] A ninth aspect includes the multilayer structure according to the first to eighth aspects, wherein the core layer is formed of Al, the conformal dielectric layer is formed of TiO2, and the conformal absorber layer is formed of W.

[0097] A tenth aspect includes the multilayer structure according to the first to eighth aspects, wherein the core layer is formed of Al, the conformal dielectric layer is formed of Fe2O3, and the conformal absorber layer is formed of W.

[0098] The eleventh aspect includes the multilayer structure of the first to tenth aspects, wherein the core layer, the conformal dielectric layer, and the conformal absorber layer each independently have a thickness less than or equal to 0.030 cm 3 / g pore volume.

[0099] A twelfth aspect includes the multilayer structure of aspects 1 to 11, wherein the core layer, the conformal dielectric layer, and the conformal absorber layer each independently have a dielectric constant less than or equal to 0.005 cm 3 / g pore volume.

[0100] A thirteenth aspect includes the multilayer structure of the first to twelfth aspects, wherein the core layer, the conformal dielectric layer, and the conformal absorber layer each independently have a dielectric constant less than or equal to 100 m 2 / g of surface area.

[0101] A fourteenth aspect includes the multilayer structure of aspects one to thirteen, wherein the core layer, the conformal dielectric layer, and the conformal absorber layer each independently have a dielectric constant less than or equal to 5 m 2 / g of surface area.

[0102] A fifteenth aspect includes the multilayer structure according to the first to fourteenth aspects, wherein the multilayer structure has a D of 1 μm to 500 μm.50 diameter.

[0103] A sixteenth aspect includes the multilayer structure according to the first to fifteenth aspects, wherein the multilayer structure has an aspect ratio of 1 to 100.

[0104] In the seventeenth aspect, a method for forming the multilayer structure of the first to sixteenth aspects comprises: depositing a conformal dielectric layer on the core layer by CVD or ALD; and depositing a conformal absorption layer on the conformal dielectric layer by ALD.

[0105] An eighteenth aspect comprises a method for forming the multilayer structure of the first to sixteenth aspects, the method comprising: depositing a conformal dielectric layer on the core layer by ALD; and depositing a conformal absorber layer on the conformal dielectric layer by ALD.

[0106] A nineteenth aspect includes a coating system comprising: a binder; and the multi-layer structure of any one of the first to sixteenth aspects.

[0107] The twentieth aspect comprises a motor vehicle having the coating system of the nineteenth aspect.

[0108] It should be noted that the terms "substantially" and "about" may be used herein to represent the inherent uncertainty that may be attributed to any quantitative comparison, value, measurement, or other representation. These terms are also used herein to represent the degree by which a quantitative representation may vary from a stated reference without resulting in a change in the basic function of the subject matter at issue.

[0109] Example

[0110] The embodiments will be further illustrated by the following examples.

[0111] Example 1

[0112] The deposition of the multilayer structure formed by the ALD process is different for each layer of the three-layer multilayer structure and is deposited as a smooth layer.

[0113] Example 2

[0114] The TiO 2 dielectric layer deposited by the ALD process of Example 1 was compared with a TiO 2 dielectric layer formed by a wet chemical process.

[0115] The pigment is suspended in isopropyl alcohol (IPA) in a flask at 40°C. A solution of titanium ethoxide dissolved in IPA is titrated at a constant rate for 2.5 hours. At the same time, DI water diluted in IPA is metered in. After titration, the suspension is stirred for another 30 minutes. The mixture is allowed to cool to room temperature, then filtered out, washed with IPA and dried at 100°C for 24 hours. The collected product is then sintered at 300°C to 500°C for a period of 2 hours to 6 hours.

[0116] The dielectric layer deposited by the ALD process of Example 1 is much smoother and denser than the dielectric layer formed by the wet chemical method.

[0117] Example 3

[0118] In this example, the effect of the thickness of the tungsten metal absorber layer and the TiO2 dielectric layer was studied. Fig. 6A Four samples prepared according to the ALD process of Example 1 are shown, except that the process is modified to provide a tungsten metal absorption layer with a thickness of 5nm, 7nm, 9nm and 12nm. All of these samples have an Al reflective core layer and a 50nm thick TiO2 dielectric layer. Fig. 6A As shown, as the thickness of the tungsten layer increases, the reflectivity curve shifts slightly to the left (shorter wavelengths), becoming more reflective.

[0119] Figure 6B Four samples prepared according to the ALD process of Example 1 are shown, except that the process is modified to provide TiO2 dielectric layers with thicknesses of 42nm, 45nm, 48nm and 50nm. All of these samples have an Al reflective core layer and a 5nm thick tungsten metal absorption layer. Figure 6B As shown, the reflectivity curve shifts slightly to the left (shorter wavelengths) as the thickness of the titanium dioxide layer increases. However, each sample performs significantly better than the seven-layer structure formed by vacuum deposition.

[0120] Example 4

[0121] This example compares the density, surface area, and pore volume of multilayer structures prepared according to the ALD process of Example 1 and the wet chemical method as described in Example 2. As shown in Table 1 below, the density of the multilayer structures prepared by ALD and wet chemical methods is the same, but the surface area of ​​the multilayer structure using the ALD method is much smaller.

[0122] Table 1

[0123] characteristic ALD method Wet chemical method density <![CDATA[2.8g / cm 3 ]]> <![CDATA[2.8g / cm 3 ]]> Surface area (BET) <![CDATA[3.6m 2 / g]]> <![CDATA[109.2m 2 / g]]> Pore ​​volume (BET) <![CDATA[0.005cm 3 / g]]> <![CDATA[0.036cm 3 / g]]>

[0124] The density of a pigment is the ratio of the mass of a pigment sample to its volume (including the contribution of the inter-particle void volume). To measure the density, a glass cylinder with a specific volume is used and a known mass of pigment is introduced into the cylinder. The volume is estimated by adding DI water to the cylinder until the water reaches the volume line of the cylinder. The volume of water is obtained by measuring the weight of the added DI water. The sample volume is obtained by subtracting the volume of water from the total volume of the cylinder. Repeat the experiment to determine the density. After degassing at 90°C for 1 hour and then at 150°C for 3 hours, a complete adsorption / desorption isotherm is collected for the sample. Isotherms are collected using nitrogen physical adsorption at 76K, and the specific surface area (SSA) of the material is obtained by fitting 13 points collected from P / P0≈0.06 to 0.3 to the Brunauer-Emmett-Teller (BET) equation. Additional adsorption points are collected at different P / P0s until P / P0≈0.95, followed by desorption back to P / P0≈0.06. The total pore volume was determined from the volume of nitrogen adsorbed at P / P0 0.95, and the average pore size was calculated using the Barrett Joyner Halenda (BJH) method.

[0125] It will be apparent to those skilled in the art that various modifications and variations may be made to the embodiments described herein without departing from the spirit or scope of the claimed subject matter. Therefore, this specification is intended to cover modifications and variations of the various embodiments described herein, as long as such modifications and variations fall within the scope of the appended claims and their equivalents.

Claims

1. A multilayer structure reflecting color, comprising: Core layer; a conformal dielectric layer encapsulating the core layer; and a conformal absorbing layer encapsulating the conformal dielectric layer, wherein The multilayer structure consists of three optical layers.

2. The multilayer structure of claim 1, wherein the multilayer structure reflects a single narrow band of visible light when exposed to broadband electromagnetic radiation, the single narrow band of visible light comprising: The single narrow band of visible light has a color shift measured in Lab color space of less than 30° when the multilayer structure is exposed to broadband electromagnetic radiation and observed at an angle of 0° to 45° relative to a normal to an outer surface of the multilayer structure.

3. The multilayer structure of claim 1, wherein the core layer is formed of Al, Ag, Pt, Sn, Au, Cu, brass, bronze, stainless steel, TiN, Cr, Al2O3, SiO2, glass, or a combination thereof. The multilayer structure according to claim 1 , wherein the core layer has a thickness of 20 nm to 100 μm.

5. The multilayer structure of claim 1, wherein the conformal dielectric layer is formed of TiO2, ZnS, ZrO2, HfO2, Fe3O4, AlAs, Fe2O3, PbS, GaAs, InAs, SiO2, MgF2, KBr, ZnO, Al2O3, and combinations thereof. The multi-layer structure of claim 1 , wherein the conformal dielectric layer has a thickness of 5 nm to 500 nm.

7. The multilayer structure of claim 1, wherein the conformal absorber layer is formed of W, Cr, Ge, Ni, stainless steel, Pd, Ti, Si, V, TiN, Co, Mo, Nb, iron oxide, or a combination thereof. The multi-layer structure of claim 1 , wherein the conformal absorber layer has a thickness of 2 nm to 50 nm.

9. The multilayer structure according to claim 1, wherein The core layer is formed of A1, The conformal dielectric layer is formed of TiO2, and The conformal absorber layer is formed of W.

10. The multilayer structure according to claim 1, wherein The core layer is formed of A1, The conformal dielectric layer is formed of Fe2O3, and The conformal absorber layer is formed of W.

11. The multilayer structure of claim 1, wherein the core layer, the conformal dielectric layer, and the conformal absorber layer each independently have a thickness less than or equal to 0.030 cm 3 / g pore volume.

12. The multilayer structure of claim 1, wherein the core layer, the conformal dielectric layer, and the conformal absorber layer each independently have a thickness less than or equal to 0.005 cm 3 / g pore volume.

13. The multilayer structure of claim 1, wherein the core layer, the conformal dielectric layer, and the conformal absorber layer each independently have a thickness less than or equal to 100 m 2 / g of surface area.

14. The multilayer structure of claim 1, wherein the core layer, the conformal dielectric layer, and the conformal absorber layer each independently have a thickness less than or equal to 5 m 2 / g of surface area.

15. The multilayer structure of claim 1, wherein the multilayer structure has a D of 1 μm to 500 μm. 50 diameter. 16 . The multilayer structure of claim 1 , wherein the multilayer structure has an aspect ratio of 1 to 100.

17. A method for forming the multilayer structure according to claim 1, the method comprising: depositing a conformal dielectric layer on the core layer by CVD or ALD; as well as A conformal absorber layer is deposited on the conformal dielectric layer by ALD.

18. A method for forming the multilayer structure according to claim 1, the method comprising: depositing a conformal dielectric layer on the core layer by ALD; as well as A conformal absorber layer is deposited on the conformal dielectric layer by ALD.

19. A coating system comprising: Binder; and The multilayer structure according to claim 1.

20. A motor vehicle comprising a coating system according to claim 19.